Karakteristik dan Pengelompokkan Perilaku Konsumen Minuman Fermentasi pada Mahasiswa - Damanik, Marisa Sara; Rasmikayati, Elly (Universitas Galuh, 2026)
Rising health awareness is driving the growth of the fermented beverage market, but consumption and processing of healthy beverages in Indonesia are still low compared to sweetened beverages. This study aims to describe the characteristics and consumer behavior of fermented beverages among college students and analyze their segmentation. This study uses a qualitative approach with a case study method through semi-structured interviews with 25 college students. The results show that consumers are dominated by young adults (19-20 years old) with good health awareness, but low consumption frequency and impulsive nature. Based on the analysis, consumers are segmented into five main groups: Health-conscious, Taste-driven, External Influence, Price-sensitive, and Convenience. It is concluded that each segment has different consumption drivers, so a differentiated marketing strategy is needed. Business actors are advised to develop product variations, educate benefits, and expand distribution to reach each segment effectively.